Green infrastructure investment opportunities Thailand 2021 report - Asian Development Bank (Manila,Philippines Asian Development Bank, 2021)
This report explores green bonds and other finance instruments for climate-resilient infrastructure and investment opportunities that can support Thailand in achieving a low carbon economy.
Executive Summary - - Green Infrastructure: An Opportunity for Growth - - Green Finance Trends and Opportunities - - Green Infrastructure Investment Opportunities in Thailand - - Measures for Growing Green Infrastructure - - Annexes.
Keywords: Sustainable development -- Thailand; Finance -- Asian Development Bank